Joyce effects on language, theory, and history - Attridge, Derek (Cambridge University Press, 2000)
Joyce Effects is a series of connected essays by one of today's leading commentators on James Joyce. Joyce's books, Derek Attridge argues, go off like fireworks, and one of this book's aims is to enhance the reader's enjoyment of these special effects. He also examines another sort of effect: the way Joyce's writing challenges and transforms our understanding of language, literature, and history. Attridge's exploration of these transforming effects represents fifteen years of close engagement with Joyce, and reflects the changing course of Joyce criticism during this period. Each of Joyce's four major books is addressed in depth, while several shorter chapters take up particular theoretical topics such as character, chance and coincidence, historical writing and narrative as they are staged and scrutinized in Joyce's writing. Through lively and accessible discussion, this book advances a mode of reading open to both the pleasures and the surprises of the literary work.
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Aufsatzsammlung; Joyce; James; Geschichte; Sprache